Rhetorical analysis of Scripture essays of the 1995 London conference - Porter, Stanley E. 1956-; Olbricht, Thomas H. (Sheffield, UK Sheffield Academic, 1997)
Includes bibliographic references and indexes.
Keywords: Biblical interpretation; Paul, Saint, the apostle -- language, style, etc; Bible. N.T. Gospels -- language, style, etc; Bible -- criticism, interpretation, etc